2015
DOI: 10.1177/1071100715572221
|View full text |Cite
|
Sign up to set email alerts
|

An Attachment-Based Description of the Medial Collateral and Spring Ligament Complexes

Abstract: The linear measurements and 3D maps may prove useful when attempting more anatomically accurate reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 31 publications
2
53
1
Order By: Relevance
“…Campbell et al demonstrated that the deep posterior tibiotalar, tibionavicular and tibiospring ligament were most consistently found in the deltoid ligament complex and that fibers from the superficial deltoid ligament coalesce with the dorsal aspect of the spring ligament (Campbell et al, 2014a). Furthermore, the tibiospring and tibionavicular ligaments, also known as the tibiocalcaneonavicular ligament (TCNL), have the largest total attachment area in the medial aspect of the medial ligament complex (Cromeens et al, 2015). Therefore, one would surmise that the TCNL provides significant medial stability to the ankle joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campbell et al demonstrated that the deep posterior tibiotalar, tibionavicular and tibiospring ligament were most consistently found in the deltoid ligament complex and that fibers from the superficial deltoid ligament coalesce with the dorsal aspect of the spring ligament (Campbell et al, 2014a). Furthermore, the tibiospring and tibionavicular ligaments, also known as the tibiocalcaneonavicular ligament (TCNL), have the largest total attachment area in the medial aspect of the medial ligament complex (Cromeens et al, 2015). Therefore, one would surmise that the TCNL provides significant medial stability to the ankle joint.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, advanced AAFD is often accompanied by a spring ligament insufficiency (Deland et al, 2005) that can lead to worsening medial instability and deltoid dysfunction despite surgical management (Deland, 2008). Recent anatomic studies suggest that spring and deltoid ligaments are not separate entities, but rather that they form a large confluent ligament, the tibiocalcaneonavicular ligament (TCNL) (Campbell et al, 2014a;Cromeens et al, 2015). Previous studies reported progressive radiographic and clinical loss of correction achieved with surgical reconstruction of Stage II AAFD (Bolt et al, 2007;Niki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two ligamentous bands comprise the deep layer of the deltoid ligament: the deep anterior and posterior tibiotalar ligaments. Generally, the deltoid ligament is known to work cooperatively and is primarily responsible for 1) stabilizing the medial side of the ankle to limit anterior, posterior, and lateral translation of the talus and 2) restraining talar abduction at the talocrural joint [2,6]. Specifically, the superficial deltoid resists eversion of the hindfoot, and the deep deltoid is the primary restraint to external rotation of the talus [5,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Two ligamentous bands make up the deep layer of the deltoid ligament: the deep anterior and posterior tibiotalar ligaments. Generally, the deltoid ligament is known to work cooperatively and is primarily responsible for 1) stabilizing the medial side of the ankle to limit anterior, posterior, and lateral translation of the talus and 2) restraining talar abduction at the talocrural joint [2,6]. Specifically, the superficial deltoid resists eversion of the hindfoot and the deep deltoid is the primary restraint to external rotation of the talus [5,7,8,9].…”
Section: Introductionmentioning
confidence: 99%